A COMUNICAÇÃO PODE SALVAR VIDAS: ALERTAS ANTECIPADOS DE EMERGÊNCIAS CLIMÁTICAS PELA TELEVISÃO DIGITAL INTERATIVA BRASILEIRA - Moreira, Fernando José Garcia (2015)
Early Emergency Warning are important elements in disaster risk reduction, avoiding the loss of life and reducing its economic impact and material. Among the most effective means of communication for the generation of early warnings, the digital television issue with capacity from one to many and with their ability to generate reactive information with data sent by the same TV signal is at the moment, the state of Art to help the population at risk, proven through comparative studies between existing emergency alert systems today around the world. This work compares the Japanese and US systems, and the theoretical framework presented focus on the communication process of an emergency information from several theories that underlie the process of communication in crisis situations, with which was reached to the conclusion that the Brazilian Digital TV technology, along with the essential infrastructure for risk detection and reliability for the generation of existing early warning, has all the necessary tools for the creation of a national system. Finally presents the initial indications for creating a model for efficient and effective communication of emergency information for the Brazilian population.